THE INFLUENCE OF DEMOGRAPHIC CHARACTERISTICS, PERCEIVED ORGANIZATIONAL SUPPORT ON AFFECTIVE COMMITMENT - Atika Aini Nasution; Bayu Eko Broto; Munawarah Munawarah (Jurnal Ekonomi, 2022)
From the initial research that researchers did, the phenomenon that occurs in the company is the number of employees who are relaxed when the work is still loose, the experts in the company feel comfortable because of the absence of rivals, as well as the lack of trust given the company to employees in providing jobs on scale the greater one. This is behind the lack of effective commitment of employees to the company. The purpose of this study is to determine the influence of demographic characteristics, length of work and perceived organizational support for affective commitment. The analysis technique used is multiple linear regression. The results showed that simultaneously the variables of demographic characteristics, work period and perceived organizational support have a significant effect on affective commitment. Demographic characteristics have no significant effect on affective commitment, tenure and perceived organizational support for affective commitment.